P5 Impact of national lung cancer awareness campaign on local referrals and outcomes in non-small cell lung cancer (NSCLC). (14th November 2013) - Calvert, LD; Chatterji, S
Abstract : Introduction: Increased awareness of lung cancer symptoms, largely due to the national 'Be Clear on Cancer' campaign in 2012 targeting smokers with cough more than 3 weeks, contributed to 14% increased lung cancer detection rates in the UK. In NSCLC, early stage and performance status at presentation are crucial to prognosis, and the impact of these initiatives on radical treatment rates needs to be reviewed. We have therefore assessed possible impact of the campaign on local detection of radically-treatable NSCLC by reviewing presenting symptoms. Methods: Patients diagnosed with NSCLC though our local thoracic oncology service in 2011 and 2012 (ie before and during the campaign) were reviewed. No other changes had been made to our diagnostic/treatment pathway between these 2 years. Results: Between 2011 and 2012, number of patient diagnosed with NSCLC increased from 140 to 162. Patients presenting with stage 1–3a and good PS 0–2 increased from 33(23.5%) to 43(26.5%), largely due to increased stage 1 disease (table 1 ). In these patients, cough was a predominant symptom in 44% (2011) and 68% (2012). In 2011, 8(24%) patients presented to GP with unexplained cough as only symptom, with average symptom length 7.5months. In 2012, 18(42%) presented with unexplained cough, 14 through GP with average symptom length 3.3months, in 7 cases under 1month. Conclusions: Our results mirror national increase in lung cancer diagnosed. We have seen an increased proportion of early stage disease, especially stage 1. Radical treatment rates increased by 6%, with curative surgery the main modality. Cough was a predominant symptom in patients presenting with radically-treatable NSCLC to their GP, and was the major focus of the national public awareness campaign in 2012. Locally, not only has the number of patients presenting with unexplained cough as a primary symptom increased between 2011 and 2012, but they are presenting sooner. It is possible therefore that the national campaign has contributed to detection of earlier stage disease in 2012 and translation to higher radical treatment rates. It will be interesting to see whether these initiatives have had similar effects on a national level and we await the LUCADA results for 2012.